Efficacy and Safety of Sphincter-Preserving Surgery in the Treatment of Complex Anal Fistula: A Network Meta-Analysis - Huang, Hua; Ji, Lijiang; Gu, Yunfei; Li, Youran; Xu, Shanshan (Frontiers in Surgery, 2022)
Background: There are many surgical methods of sphincter preservation in the treatment of complex anal fistula, but the therapeutic effects of each operation are different. Therefore, this study aimed to compare the effects of different treatment methods through a network meta-analysis to evaluate the best sphincter preservation method for the treatment of complex anal fistula. Methods: We searched PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, VIP Journal Database, and the Wanfang Database to collate randomized controlled trials on sphincter-preserving surgery for complex anal fistula. Results: A total of 29 articles were included in this meta-analysis. The results of the cure rates showed no statistically significant differences between any two interventions (P > 0.05). The results of the recurrence rate showed that the rate of patients after Fistulectomy was higher than others(P < 0.05). The results of the incidence rate of complications showed that the incidence rate after Fistulectomy treatment was higher than that of others (P < 0.05). The results showed that TROPIS had the highest probability ranking of cure rate (78.6%), Stem cell transplantation(SCT) had the highest probability ranking of recurrence rate (85.5%), and imLIFT had the highest probability ranking of postoperative complications (88.2%). Conclusion: According to the existing literature data, for patients with complex anal fistula, TROPIS may be the surgical method with the highest cure rate, SCT may be the treatment method with the lowest recurrence rate, and imLIFT may be the surgical method with the lowest incidence of postoperative complications.